2D MoS2: structure, mechanisms, and photocatalytic applications. (September 2021) - Thomas, N.; Mathew, S.; Nair, K.M.; O'Dowd, K.; Forouzandeh, P.; Goswami, A.; McGranaghan, G.; Pillai, S.C.
Abstract: Two-dimensional (2D) molybdenum disulfide (MoS2 )–based materials are of great interest because of their capacity to efficiently absorb electromagnetic spectrum in the visible region. Starting from the structural and electronic properties, this review discusses the synthesis strategies of 2D MoS2 . The major photocatalytic applications of 2D MoS2 such as hydrogen evolution, pollutant degradation, self-cleaning, photoelectrochemical water splitting, and microbial disinfection are summarized. The mechanistic understanding of various photocatalytic applications of 2D MoS2 is summarized through schematic diagrams. In addition, this review outlines the methodologies for improving the 2D MoS2 photocatalysts and recapitulates the research directions in this area of semiconductor photocatalysis. Graphical abstract: Image 1 Highlights: Photocatalytic mechanisms and applications of two-dimensional (2D) MoS2 are detailed. Strategies for tuning the electronic and optical properties of 2D MoS2 . Synthesis protocols and photoelectrochemical studies of 2D MoS2 are summarised. MoS2 composites for enhancing photocatalytic hydrogen production are detailed. 2D MoS2 -based materials for contaminant degradation and disinfection are discussed.